2017
DOI: 10.1089/jop.2016.0092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short-Term Effects of Diquafosol and Rebamipide on Mucin 5AC Level on the Rabbit Ocular Surface

Abstract: These data indicated that more PAS-positive MUC5AC was released into the tear fluid from the goblet cells by diquafosol than by rebamipide. There is a difference in the induction pattern of MUC5AC into the tears from the goblet cells between these eye drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…DQS is reported to promote not only tear secretion but also mucin secretion. 33 Because DQS increased both of these secretions might be attributable to the increase in tear stability in terms of tear quality and tear quantity, resulting in improvement of corneal epithelial damage. In this study, mucin secretion increase by DQS was not measured; however, an increase in mucin secretion could underlie the observed improvement in corneal epithelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…DQS is reported to promote not only tear secretion but also mucin secretion. 33 Because DQS increased both of these secretions might be attributable to the increase in tear stability in terms of tear quality and tear quantity, resulting in improvement of corneal epithelial damage. In this study, mucin secretion increase by DQS was not measured; however, an increase in mucin secretion could underlie the observed improvement in corneal epithelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…71 We also compared the short-term effects on the MUC5AC level in rabbit tear fluid and conjunctival goblet cells after instilling both eyedrops. 50 Only diquafosol increased the MUC5AC level 15 minutes after one instillation. 50 These results suggested that diquafosol promotes rapid secretion of MUC5AC from conjunctival goblet cells into the tear film after instillation.…”
Section: Comparison Of Diquafosol and Rebamipidementioning
confidence: 96%
“…50 Only diquafosol increased the MUC5AC level 15 minutes after one instillation. 50 These results suggested that diquafosol promotes rapid secretion of MUC5AC from conjunctival goblet cells into the tear film after instillation. We hypothesized that diquafosol might improve tear fluid stability in the short term with its stimulatory effect on the tear fluid and mucin secretion via the P2Y2 receptor; on the other hand, rebamipide might improve the mucosal epithelia and increase the goblet cell numbers, which cure the ocular surface in patients with dry eye.…”
Section: Comparison Of Diquafosol and Rebamipidementioning
confidence: 96%
See 1 more Smart Citation
“…6,7 In addition, diquafosol sodium increases tear volume and stimulates mucin secretion by secretary goblet cells, 7,8 as previously observed in animal models. [9][10][11][12][13] However, diquafosol does not directly act on the lacrimal glands or stimulate protein secretion. 14 Moreover, diquafosol upregulates the expression of membrane-binding mucin genes in corneal epithelial cells.…”
Section: Diquafosolmentioning
confidence: 99%